2022
DOI: 10.1149/2754-2726/ac8437
|View full text |Cite
|
Sign up to set email alerts
|

MnO2-SnO2 Based Liquefied Petroleum Gas Sensing Device for Lowest Explosion Limit Gas Concentration

Abstract: An MnO2-SnO2 nanocomposite-based sensing device with below lower exposure limit (0.5-2.0 vol%) for liquefied petroleum gas (LPG) is reported. The synthesized material is highly crystalline with an average crystallite size of 16.786 nm, confirmed by the X-ray diffraction (XRD). A Williamson-Hall plot shows that induced strain of 2.627×10-4, present in the nanocomposite, lies between the induced strains of both of its constituents. The XRD pattern of nanocomposite contains cubic phase of MnO2 and the tetragonal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 50 publications
0
21
2
Order By: Relevance
“…However, MRGO 12H sensor had outstanding response and recovery time superior to PRGO 12H and NRGO 12H, thus indicating superior material selectivity towards sensing LPG compared to NRGO 12H and PRGO 12H. While reports have been made on how high operating temperature of sensors results in reduced response time and large recovery time, 28 at a low operating temperature of 30 °C, we have obtained response time that are far below reported values in several literature 9,37,39,40 while recovery time of the sensors ranged between 6.46 seconds and 41.50 seconds. MRGO 12H sensor typified the least recovery time and thus outperformed results from reported literature.…”
Section: Resultscontrasting
confidence: 69%
“…However, MRGO 12H sensor had outstanding response and recovery time superior to PRGO 12H and NRGO 12H, thus indicating superior material selectivity towards sensing LPG compared to NRGO 12H and PRGO 12H. While reports have been made on how high operating temperature of sensors results in reduced response time and large recovery time, 28 at a low operating temperature of 30 °C, we have obtained response time that are far below reported values in several literature 9,37,39,40 while recovery time of the sensors ranged between 6.46 seconds and 41.50 seconds. MRGO 12H sensor typified the least recovery time and thus outperformed results from reported literature.…”
Section: Resultscontrasting
confidence: 69%
“…The resistance of sensor was increased/decreased depends on n-type or ptype due to the adsorption/desorption of analyte. 29 It was observed that the resistance of the GPoP sensor was increased with the increasing RH due to the presence of hydrophilic functional groups present on graphite surface as it is explained by Alrammouz et al 30 and Choo et al 31 The water molecules connect to the hydrophilic functional groups on its surface by removing electrons when they interact with these groups as a result of which they become less conductive in higher RH. As explained by, 32 the resistance of sensor is increasing with the increased RH because the sensing material will be a p-type material due to which absorption of water molecules will be acting as electron donor, so decrease of hole concentration due to water molecules and due to swelling of bare paper.…”
Section: Discussionmentioning
confidence: 94%
“…39 The peaks of the ZnSnO 3 appear at 26.44°, 31.61°, 34.06°, 36.29°, 51.66°, 57.61°, and 65.54°c orrespond to diffraction planes as (110), (012), ( 104), (015), ( 116), (214), and (036) respectively. The crystallite size of the ZnSnO 3 was calculated by Scherrer formula, 40 and the average crystallite size was found to be 8.05 nm. When the crystalline dimension of the material goes below 20 nm, the nanostructure dimension allows all atoms to be within the Debye length of the material.…”
Section: Resultsmentioning
confidence: 99%